Mechanisms involved in the cytotoxic action of Brazilian propolis and caffeic acid against HEp-2 cells and modulation of P-glycoprotein activity - da Silva, Lívia M. [UNESP]; Frión-Herrera, Yahima [UNESP]; Bartolomeu, Ariane R. [UNESP]; Gorgulho, Carolina Mendonça [UNESP]; Sforcin, José M. [UNESP] (Oxford University Press (OUP), 2017)
Objectives: The effects of propolis and phenolic compounds (caffeic acid – Caf; dihydrocinnamic acid – Cin; p-coumaric acid – Cou) in the same quantity found in our propolis sample were investigated on human laryngeal epidermoid carcinoma (HEp-2) cells. Methods: Cell viability, apoptosis/necrosis and cell cycle arrest, P53 and CASPASE-3 gene expression, generation of reactive oxygen species (ROS) and the ability of propolis to induce doxorubicin (DOX) efflux using a P-glycoprotein (P-gp) inhibitor (verapamil) were assayed. Key findings: Propolis exerted a cytotoxic effect on HEp-2 cells, whereas isolated compounds had no effect on cell viability. Higher concentrations were tested and Caf induced late apoptosis or necrosis in HEp-2 cells, while propolis induced apoptosis, both probably due to ROS generation. P53 expression was downregulated by propolis but not by Caf. CASPASE-3 expression was correlated with induction of both early and late apoptosis, with both propolis and Caf alone upregulating its expression. Propolis induced cell cycle arrest at G2/M phase and Caf at S phase. Propolis but not Caf may act as a P-gp inhibitor by modulating P-gp activity and inhibiting DOX efflux. Conclusions: Propolis exerted cytotoxic effects on HEp-2 cells, and the mechanisms are discussed, showing its potential as an antitumour drug.
Keywords: caffeic acid; HEp-2 cells; P-glycoprotein; phenolic compounds; propolis